2022
DOI: 10.1002/brb3.2836
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin upregulates BMAL1 to attenuate chronic sleep deprivation‐related cognitive impairment by alleviating oxidative stress

Abstract: Purpose: To investigate the mechanism underlying the regulatory effect of melatonin on chronic sleep deprivation-related cognitive impairment.Methods: Chronic sleep deprivation (CSD) model was established using the MMPM method. After the model was established, melatonin receptor agonist and inhibitor were given, respectively. Water maze was conducted to record the escape latency and the duration of crossing the platform of space exploration. The concentration of TNF-α, IL-6, MDA, and SOD was measured by ELISA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…SIRT1, a deacetylase enzyme, plays a key role in regulating the central circadian rhythm in the SCN by promoting the transcription of the main circadian regulators, BMAL1 and CLOCK. These circadian regulators are also regulated by melatonin to alleviate oxidative stress and attenuate cognitive impairment after sleep deprivation (Chang and Guarente 2013 ; Hu et al 2023 ). Farnesol, a natural sesquiterpenoid, exerts neuroprotective effects against sleep deprivation-induced cognitive impairment by activating the SIRT1/NRF2 signaling pathway.…”
Section: Modulation Of Nrf2 In Sleep Disruptionmentioning
confidence: 99%
“…SIRT1, a deacetylase enzyme, plays a key role in regulating the central circadian rhythm in the SCN by promoting the transcription of the main circadian regulators, BMAL1 and CLOCK. These circadian regulators are also regulated by melatonin to alleviate oxidative stress and attenuate cognitive impairment after sleep deprivation (Chang and Guarente 2013 ; Hu et al 2023 ). Farnesol, a natural sesquiterpenoid, exerts neuroprotective effects against sleep deprivation-induced cognitive impairment by activating the SIRT1/NRF2 signaling pathway.…”
Section: Modulation Of Nrf2 In Sleep Disruptionmentioning
confidence: 99%
“…These lesional effects are closely associated with neuritis caused by excessive microglial activation [ 32 ]. Chronic SD promotes the transformation of microglia into the neurotoxic M1 phenotype and subsequently induces the NF-κB pathway to increase the release of pro-inflammatory factors (TNF-α, IL-6), causing neuroinflammatory response, aggravating hippocampal neuron damage, and affecting cognitive function [ 55 ]. Further studies found that SD increased the protein levels of the pro-inflammatory cytokines TNF-α, IL1-β, IL-6, and IL-8 but decreased the protein levels of the anti-inflammatory cytokines IL-4 and IL-10 in the rat hippocampus [ 55 , 57 , 102 , 103 , 104 ].…”
Section: Potentially Relevant Mechanismsmentioning
confidence: 99%
“…Chronic SD promotes the transformation of microglia into the neurotoxic M1 phenotype and subsequently induces the NF-κB pathway to increase the release of pro-inflammatory factors (TNF-α, IL-6), causing neuroinflammatory response, aggravating hippocampal neuron damage, and affecting cognitive function [ 55 ]. Further studies found that SD increased the protein levels of the pro-inflammatory cytokines TNF-α, IL1-β, IL-6, and IL-8 but decreased the protein levels of the anti-inflammatory cytokines IL-4 and IL-10 in the rat hippocampus [ 55 , 57 , 102 , 103 , 104 ]. Serum levels of pro-inflammatory cytokines (IL-6, IL-1β, TNF-α) increased in SD rats after 24 h of SD, and the effect was more significant in cerebrospinal fluid after 72 h of SD (IL-1β: 30.2 ± 12.8 pg·mL −1 →43.6.8 ± 9.4 pg·mL −1 ; IL-6: 28.8 ± 9.3 pg·mL −1 →37.8 ± 7.4 pg·mL −1 ; TNF-α:19.1 ± 6.3 pg·mL −1 →21.8 ± 7.4 pg·mL −1 ).…”
Section: Potentially Relevant Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations